(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluation of response and toxicity of vinorelbine algorithm in patients with stage IV non-small cell lung cancer at Thong Nhat Hospital’s Oncology Department. Methods: Retrospective descriptive case series in 1/2019-6/2022. Results: in 3.5 years 2019 and 2022, retrospectively 43 cases using vinorelbine chemotherapy was divided into 2 groups including 25 patients on first-line treatment and 18 patients on second-line treatment, overall response rate was 44.2%; median duration of response was 15 months; median progression-free survival was 6 months; median overall survival was 8 months; overall 1-year survival rate was 27.9%. Conclusion: metronomic vinorelbine is effective and safe.